The Mediating Role of Organizational Citizenship Behavior in the Relationship Between Social Interaction, Knowledge Management, and Employee Job Satisfaction at Bank BCA East Java - Natalia Ellianasari Putri Setiawan; Roby Nur Akbar (Business Management Research, 2025)
This study investigates the influence of social interaction and knowledge management on employee job satisfaction, mediated by Organizational Citizenship Behavior (OCB), within Bank BCA in East Java during 2024. Employing a quantitative research design, primary data were collected through online questionnaires administered to employees across 36 Bank BCA branches in East Java, selected via purposive sampling. Data analysis involved descriptive statistics, validity and reliability tests, discriminant variable tests, and model fit assessment using the PLS application, with SRMR (Standardized Root Mean Square Residual) utilized for enhanced model accuracy. The findings reveal that not all hypothesized relationships are significant. Specifically, knowledge management does not exert a direct significant effect on job satisfaction. Furthermore, the indirect effect of social interaction on job satisfaction, through OCB as a mediating variable, was also found to be non-significant. These results challenge common assumptions regarding the direct and indirect impacts of social and knowledge-related factors on job satisfaction in a banking context, highlighting the complexity of organizational behavior in practice.